Pengaruh Intensitas Nyeri Punggung Bawah Terhadap Derajat Keterbatasan Aktivitas - Ivana Felicia; Arwinder Singh (Universitas Malahayati, 2025)
ABSTRACT Low back pain is one of the most common musculoskeletal disorders and a leading cause of disability globally, which can lead to limitations in daily activities for both working individuals and the elderly population. This study aims to determine the relationship between the intensity of low back pain and the level of activity limitation in affected individuals. The research employs a cross-sectional design with 170 respondents selected through consecutive random sampling, where data were collected through interviews and questionnaires using the Numeric Rating Scale to measure pain intensity and the Oswestry Disability Index to assess the level of disability. The study was conducted at Sumber Waras Hospital and Dr. Mintohardjo Naval Hospital, with data analysis performed using univariate analysis (frequency distribution) and bivariate analysis using the chi-square test. The results show that the majority of individuals with severe pain intensity fall into the high disability category, with 41.1% classified as Crippled and 19.6% as Bed-bound or Exaggerating Symptoms, indicating a significant relationship between pain intensity and disability level (p 0.001). In conclusion, the intensity of low back pain is significantly related to the level of disability, highlighting the importance of pain management to improve the quality of life for patients. Keywords: Low Back Pain, Pain Intensity, Level of Disability, Relationship Between Pain And Disability. ABSTRAK Nyeri punggung bawah merupakan salah satu gangguan muskuloskeletal yang paling umum terjadi dan menjadi penyebab utama disabilitas secara global, yang dapat menyebabkan keterbatasan aktivitas sehari-hari pada individu yang aktif bekerja maupun populasi lansia. Penelitian ini bertujuan untuk menentukan hubungan antara intensitas nyeri punggung bawah dengan tingkat keterbatasan aktivitas pada individu yang mengalaminya. Penelitian menggunakan desain cross sectional dengan 170 responden yang dipilih secara consecutive random sampling, di mana data dikumpulkan melalui wawancara dan kuesioner menggunakan Numeric Rating Scale untuk mengukur intensitas nyeri dan Oswestry Disability Index untuk menilai tingkat disabilitas. Penelitian dilakukan di Rumah Sakit Sumber Waras dan Rumah Sakit Angkatan Laut dr. Mintohardjo dengan analisis data univariat (distribusi frekuensi) dan bivariat menggunakan uji chi-square. Hasil menunjukkan mayoritas individu dengan intensitas nyeri berat berada pada kategori disabilitas tinggi, yaitu 41,1% hampir lumpuh dan 19,6% lumpuh, dengan hubungan yang signifikan antara intensitas nyeri dan tingkat disabilitas (p 0,001). Kesimpulannya, intensitas nyeri punggung bawah berhubungan secara signifikan dengan tingkat disabilitas, yang menunjukkan pentingnya pengelolaan nyeri untuk meningkatkan kualitas hidup penderita. Kata Kunci: Nyeri Punggung Bawah, Intensitas Nyeri, Tingkat Disabilitas, Hubungan Nyeri dan Disabilitas